ACTIVE POWER FACTOR CORRECTION USING A SLIDING MODE CONTROLLER - Kayisli, Korhan; Tuncer, Servet; Poyraz, Mustafa (Pamukkale Univ, 2008)
In this paper, a sliding mode controller is designed for active shaping of the input current in the boost converter. Robustness of the designed controller is tested with variable output voltage references, different loads and network voltage variations. For the simulations, MATLAB/Simulink programme is used. From simulation results, the same phase was provided between input current and input voltage and nearly unity power factor was obtained.
Keywords: Power factor correction; Boost type converter; Sliding mode controller